Comparison of Workgroup Serrated Polyps and Polyposis (WASP) classification of colorectal polyps evaluated with blue laser imaging against histopathological diagnosis - Lamichhane, Kamal; Shrestha, Ramila; Khadka, Dibas (Journal of Chitwan Medical College, 2025)
Introduction: Colorectal polyps are precursors of colorectal carcinoma. Virtual chromo endoscopy and classification systems have improved real-time diagnosis. This study compared diagnostic accuracy of Workgroup serrAted polypS and Polyposis (WASP) classification using Blue Laser Imaging (BLI) against histopathological examination (HPE).Method: An observational study was conducted at Bir Hospital, Nepal (Feb 2024-Apr 2025). Colorectal polyps detected during colonoscopy were examined under white light and BLI to classify using WASP. Patients' demographics (age, gender) and polyp characteristics (site, size, number, type) were recorded. Resected polyps were sent for HPE. Diagnostic performance (sensitivity, specificity, predictive values, and accuracy) was calculated in reference to HPE. Data analysis was performed using SPSS v26; p≤0.05 was considered significant at 95% CI.Result: Eighty-six colorectal polyps from 62 patients (mean age 54.4 years, 66.1% male) were evaluated. Diminutive polyps (≤5 mm) were 58(67.4%) and 56(65.1%) left-sided. By WASP classification, 64(74.4%) were hyperplastic, 21(24.4%) adenomatous, and 1(1.2%) sessile serrated adenoma/polyp. Histopathology confirmed 27(31.4%) adenomatous polyps, of which 18(66.7%) were left-sided. For adenomatous polyps, BLI-WASP demonstrated 59.3% sensitivity, 91.5% specificity, 76.2% PPV, 83.1% NPV and 81.4% accuracy. Hyperplastic polyps were identified with 100% sensitivity and 37.3% specificity. In diminutive adenomatous polyps, diagnostic accuracy was 81.0%. There was a significant association between WASP classification and histopathology (p